KONTRIBUSI POSDAYA MASJID âMIFTAHUL HIDAYAHâ DI DESA BULAY KECAMATAN GALIS KABUPATEN PAMEKASAN - Nashar, Nashar; Wardi, Moch. Cholid; Listiana, Heni (STAIN PAMEKASAN, 2017)
The concept of poverty alleviation is not solely a matter for government but has become the responsibility of the congregation. Action against poverty is jihad in the path of Allah Swt. It seems Empowerment Center has changed the pattern of relations between officials at the village level or the district, employers, the profession with the congregation in the mosque which was originally a pattern of relationships out sider in-sider, different interests, patterns of kinship, common interest to transform the society into a prosperous self-sufficient. Through Empowerment Center of the mosque, it is expected that a number of poor families successfully assisted to the strengthening of entrepreneurship and access to capital through the funds of the mosque, funds Lakzis, BMT, and the bank of SMES with a system of joint responsibility. Another positive thing happens with the optimal the Mosque based Empowerment CenterÂ is increasing the confidence of isoleted society. They have friends from diverse elements of the good academics, the professions, local officials and local leaders are easily accessible and are invited to the discussion. Based on that, then there are three problems that become the basic study in this study, namely: first, how is the strategy of Empowerment Center in conducting empowerment in the community?, second what are the contributions of Empowerment Center of the mosque and the third, what became the Empowerment Center of the mosque âMiftahul Hidayahâ selected to be Posdaya National referral 2016 ?The theory of Empowerment that is worn according to the meaning in language is a process, a way, the deeds make the helpless, namely the ability to do something or ability to act in the form of common sense, endeavor or effort, community is the unity of human life that interact according to a system of certain mores that are continuous, and which is bound by a sense of shared identity, in some of the studies regarding the construction of community, community empowerment is often interpreted as an attempt to give power so their voices heard in order to contribute to the planning and decisions that affect their community, community empowerment can be interpreted as an attempt to restore or improve the ability of a community to be able to do in accordance with the dignity in implementing their rights and responsibilities as members of the community.